Multidimensional Impact of Overweight on Quality of Life of Children and Adolescents: A Scoping Review - Iin Utami Yasrianti Lamukara; Nur Setiawati Dewi; Rita Hadi Widyastuti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Overweight in adolescents is a global health issue that has shown a significant increase in recent decades. This condition has a multidimensional impact, particularly on the physical, psychological, social aspects, and overall quality of life of adolescents. Children and adolescents who are overweight often experience body shaming, social stigma, decreased self-esteem, and social isolation, all of which can contribute to a lower quality of life. Although numerous studies have explored the relationship between being overweight and quality of life, most have focused only on physical or psychological dimensions. Many of the existing studies examine just one or two aspects of quality of life and lack a comprehensive consideration of cultural factors, developmental age, and social interactions. Objective to comprehensively review the scientific literature that examines the impact of overweight on the quality of life among adolescents. This study employed a scoping review approach based on the PRISMA-ScR guidelines. Literature searches were conducted through three databases: Scopus, PubMed, and ScienceDirect, using the keywords